Insights Into the Hypometabolic Stage Caused by Prolonged Starvation in L4-Adult Caenorhabditis elegans Hermaphrodites - Carranza-García, E.; Navarro, Rosa E. (Frontiers in Cell and Developmental Biology, 2020)
Germ cells are the basis for species continuity. Animals adapt their reproductive cycle in response to changing nutritional conditions, to develop and ensure offspring production only under favorable conditions. These adaptive strategies include reversible hypometabolic states of dormancy that include “arrest” and “diapause”. Although the free-living nematode C. elegans can arrest its life-cycle during some larval stages without modifying its anatomy and physiology until conditions improve; it can also modify its morphology and physiological features to cope with harsh conditions and develop into a diapause. The well-defined “dauer” diapause was described more than 40 years ago and has been the subject of comprehensive investigations. The existence of another hypometabolic state, termed the adult reproductive diapause (ARD), has been debated after it was described for the first time 10 years ago. Here, we review the current knowledge regarding the effect of food deprivation during the pre-reproductive larval and adult stages on overall organismal homeostasis, highlighting the implications on germ cell maintenance and fertility preservation.